Teenage Marriage Age Survey Survei Umur Ingin Menikah pada Remaja - Setyawati, Irni; Utami, Kusniyati; Adithia Pratiwi, Eka (Journal of Fundus, 2024)
Marriage is the physical and mental bonding of a man and a woman as husband and wife with the aim of forming a happy and lasting family based on God Almighty. Marriage is permitted by the laws and regulations in force in Indonesia since 2019, namely marriage is permitted if the man and woman have reached the age of 19 years. From the results of simple interviews with 10 students at STIKes Yarsi Mataram, 80% stated that they were dating, and 20% of students were not dating. From the results mentioned above, the researcher is interested in conducting a survey of the age of wanting to get married at STIKes Yarsi Mataram. This study used an observational survey design with a cross-sectional time approach. This research was conducted in March 2024 at STIKes Yarsi Mataram. The sample obtained was 176 people. Data analysis using univariate and bivariate analysis. The results showed that there was a significant difference in the age of wanting to get married based on father's education as indicated by a p value of 0.011 (p <0.05). There was a significant difference in the age of wanting to get married based on the desire to get married quickly as indicated by a p value of 0.001. There is a need for continuous and consistent education on risky dating behaviour and Islamic religious views on dating to university students.